Efek Keadilan Remunerasi, Kompetensi Atasan dan Kohesivitas Kelompok terhadap Withholding Effort - Ida Ayu Kartika Maharani; I Gede Riana; I Gede Adnyana Sudibya (Institute of Research and Community Outreach - Petra Christian University, 2016)
Withholding effort is a tendency employee to reduce work contribution as the possibility of an individual in giving less than maximum effort on tasks associated with the job. The purpose of this study is to analyze the remuneration fairness influences, supervisor competencies and group cohesiveness on withholding effort. The population in this study was all administrative employees with the status of civil servants and probationary civil servants who were actively working in the Institute Hindu Dharma Negeri Denpasar. The number of respondents were 80 people. The research data was primary data obtained from questionnaires. This study used confirmatory factor analysis and multiple linear regression analysis as analytic technique. The results show that fairness of remuneration has a negative and significant effect on the withholding effort, supervisor competencies has a negative and significant effect on the withholding effort, group cohesiveness has a negative and significant effect on the withholding effort.